2021
DOI: 10.1073/pnas.2019128118
|View full text |Cite
|
Sign up to set email alerts
|

Cingulo-opercular control network and disused motor circuits joined in standby mode

Abstract: Whole-brain resting-state functional MRI (rs-fMRI) during 2 wk of upper-limb casting revealed that disused motor regions became more strongly connected to the cingulo-opercular network (CON), an executive control network that includes regions of the dorsal anterior cingulate cortex (dACC) and insula. Disuse-driven increases in functional connectivity (FC) were specific to the CON and somatomotor networks and did not involve any other networks, such as the salience, frontoparietal, or default mode networks. Cen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 51 publications
13
31
1
Order By: Relevance
“…In our consensus network structure, we found that the cingulo-opercular network received significant connections from the somatomotor network, sent significant connections to the orbito-affective (reward) network, and was bidirectionally connected to the frontoparietal network. The uncovered functional connectivity between the reward and cingulo-opercular networks is in line with evidence that cingulo-opercular network has an important role in coordinating the response of brain reward-related regions (Huckins et al, 2019), and the connectivity between the cingulo-opercular and somatomotor networks corroborates evidence that the cingulo-opercular network plays a role in consolidation, planning, and plasticity of motor regions (Newbold et al, 2021). Connectivity between cingulo-opercular and somatomotor networks also increases through development and is linked to the development of improved cognitive control (Marek et al, 2015).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our consensus network structure, we found that the cingulo-opercular network received significant connections from the somatomotor network, sent significant connections to the orbito-affective (reward) network, and was bidirectionally connected to the frontoparietal network. The uncovered functional connectivity between the reward and cingulo-opercular networks is in line with evidence that cingulo-opercular network has an important role in coordinating the response of brain reward-related regions (Huckins et al, 2019), and the connectivity between the cingulo-opercular and somatomotor networks corroborates evidence that the cingulo-opercular network plays a role in consolidation, planning, and plasticity of motor regions (Newbold et al, 2021). Connectivity between cingulo-opercular and somatomotor networks also increases through development and is linked to the development of improved cognitive control (Marek et al, 2015).…”
Section: Discussionsupporting
confidence: 83%
“…The copyright holder for this preprint this version posted October 21, 2021. ; https://doi.org/10.1101/2021.10.20.465211 doi: bioRxiv preprint the reward and cingulo-opercular networks is in line with evidence that cingulo-opercular network has an important role in coordinating the response of brain reward-related regions (Huckins et al, 2019), and the connectivity between the cingulo-opercular and somatomotor networks corroborates evidence that the cingulo-opercular network plays a role in consolidation, planning, and plasticity of motor regions (Newbold et al, 2021). Connectivity between cingulo-opercular and somatomotor networks also increases through development and is linked to the development of improved cognitive control (Marek et al, 2015).…”
Section: Discussionsupporting
confidence: 79%
“…These networks underlie the dual control of executive functions [73] and have been shown to be functionally coupled also in the resting state [74] which is in agreement with the role of DA in cognitive control [70,75]. Further, our results are in line with brain-wide distribution of catecholamine-induced changes in DA and NE in intrinsic fMRI correlations [21] and with findings that DA innervation covers the entire cortex [76] and Locus Coeruleus' NE projections reach a variety of targets [69].…”
Section: Local Oscillation Strength and Dynamics Are Modulated By Genetic Polymorphism In Comt And Bdnfsupporting
confidence: 88%
“…We utilized both the Midnight Scan Club (MSC) dataset (n = 10 participants; 300 min. of resting-state fMRI data/subject) (34) and additional extremely highly sampled, higher-resolution resting-state fMRI data (2.6 mm isotropic voxels; 2,610 min; MSC06-Rep) from an independent dataset (57,58). We generated individual-specific RSFC parcellations of the hippocampus, drawing on several advantages over group-averaging, including the following: (1) higher signal-to-noise ratio in deeper subcortical structures without blurring individual differences in network features and (2) more precise definition of individual-specific cortical functional network maps (i.e., DMN, PMN, CAN, and FPN).…”
Section: Significancementioning
confidence: 99%